Functional MRI in clinical practice: Assessment of language and motor for pre-surgical planning. Issue 5 (October 2015) - Mahdavi, Ali; Azar, Ramyar; Shoar, Majid Haghighat; Hooshmand, Sina; Mahdavi, Arash; Kharrazi, Homayoon Hadizadeh
Functional magnetic resonance imaging (fMRI) has been widely used for pre-neurosurgical planning and may eventually become a routine pre-surgical imaging modality. The validity of fMRI for clinical application depends on various factors such as proper task selection, correct statistical analysis and threshold setting with appropriate patient cooperation. This study was performed on 40 patients with different types of brain mass lesions or hippocampal sclerosis to assess the role of appropriate patient selection for achieving a reliable fMRI result. Accurate and reproducible fMRI strongly depends on the patient's cooperation. In this study we observed that a pre-test mock fMRI session held by a radiologist may help to predict which patients are more or less suitable candidates for fMRI.